Chemical, Cytotoxic, and Anti-Inflammatory Assessment of Honey Bee Venom from Apis mellifera intermissa - Iouraouine El Mehdi; Soraia I. Falcão; Mustapha Harandou; Saïd Boujraf; Ricardo C. Calhelha; Isabel C. F. R. Ferreira; Ofélia Anjos; Maria G. Campos; Miguel Vilas-Boas (MDPI AG, 2021)
The venom from Apis mellifera intermissa, the main honey bee prevailing in Morocco, has been scarcely studied, despite its known potential for pharmacological applications. In the present work, we investigated the composition, the anti-inflammatory activity, and the venom's cytotoxic properties from fifteen honey bee venom (HBV) samples collected in three regions: northeast, central, and southern Morocco. The chemical assessment of honey bee venom was performed using LC-DAD/ESI/MSn, NIR spectroscopy and AAS spectroscopy. The antiproliferative effect was evaluated using human tumor cell lines, including breast adenocarcinoma, non-small cell lung carcinoma, cervical carcinoma, hepatocellular carcinoma, and malignant melanoma. Likewise, we assessed the anti-inflammatory activity using the murine macrophage cell line. The study provides information on the honey bee venom subspecies' main components, such as melittin, apamin, and phospholipase A2, with compositional variation depending on the region of collection. Contents of toxic elements such as cadmium, chromium, and plumb were detected at a concentration below 5 ppm, which can be regarded as safe for pharmaceutical use. The data presented contribute to the first study in HBV from Apis mellifera intermissa and highlight the remarkable antiproliferative and anti-inflammatory effects of HBV, suggesting it to be a candidate natural medicine to explore.